Psychophysical Evaluation of Haptic Perception Under Augmentation by a Handheld Device. (May 2015) - Wu, Bing; Klatzky, Roberta; Lee, Randy; Shivaprabhu, Vikas; Galeotti, John; Siegel, Mel; Schuman, Joel S.; Hollis, Ralph; Stetten, George
Objective: This study investigated the effectiveness of force augmentation in haptic perception tasks. Background: Considerable engineering effort has been devoted to developing force augmented reality (AR) systems to assist users in delicate procedures like microsurgery. In contrast, far less has been done to characterize the behavioral outcomes of these systems, and no research has systematically examined the impact of sensory and perceptual processes on force augmentation effectiveness. Method: Using a handheld force magnifier as an exemplar haptic AR, we conducted three experiments to characterize its utility in the perception of force and stiffness. Experiments 1 and 2 measured, respectively, the user's ability to detect and differentiate weak force (<0.5 N) with or without the assistance of the device and compared it to direct perception. Experiment 3 examined the perception of stiffness through the force augmentation. Results: The user's ability to detect and differentiate small forces was significantly improved by augmentation at both threshold and suprathreshold levels. The augmentation also enhanced stiffness perception. However, although perception of augmented forces matches that of the physical equivalent for weak forces, it falls off with increasing intensity. Conclusion: The loss in the effectiveness reflects the nature of sensory and perceptual processing. Such perceptual limitations should be taken into consideration in the design and development of haptic AR systems to maximize utility. Application: The findings provide useful information for building effective haptic AR systems, particularly for use in microsurgery.